Frailty affects prognosis in patients with colorectal cancer: A systematic review and meta-analysis - Cai, Minghao; Gao, Zhongyan; Liao, Junyi; Jiang, Yuanping; He, Yong (Frontiers in Oncology, 2022)
Background The prevalence of colorectal cancer has remained high. Most patients have already developed into the middle and advanced stage when they are diagnosed with colorectal cancer, and a small number of them are accompanied by metastasis. In recent years, frailty has been recognized as an important factor affecting the prognosis of colorectal cancer. The aim of this study was to assess the value of frailty on prognosis in patients with colorectal cancer after treatment. Method We systematically searched PubMed, Embase, Web Of Science databases up until March2022. A total of 18 studies were retrieved that met the inclusion criteria, including 9 prospective studies and 9 retrospective studies. Frailty screening tools, proportion of frail patients, and outcomes of colorectal cancer patients after treatment were recorded. Result 18 studies were included with a total of 352,535 participants. Regardless of differences in frailty screening and treatment approaches, outcomes for frailty patients were less favorable in all studies. Compared with the non-frail group, the frail group had higher mortality, more serious complications, more postoperative blood transfusions and delirium, and more support outside the home. Conclusion Although there is no uniform standard for frailty screening, assessing the frailty of colorectal cancer patients is of great significance for predicting prognosis of patients after treatment.